Outcomes of Posterior Glenoid Bone-Grafting in Anatomical Total Shoulder Arthroplasty: A Systematic Review. Issue 9 (September 2019) - Gates, Stephen; Cutler, Holt; Khazzam, Michael
Abstract : Background: Total shoulder arthroplasty offers a reliable means with which to treat glenohumeral joint arthritis. Posterior glenoid bone loss presents a unique challenge with an increased risk of glenoid component failure. The use of posterior bone-grafting is one method to address glenoid bone loss in patients undergoing anatomical total shoulder arthroplasty. The purpose of the present study was to assess the outcome and survival of the glenoid component following the use of bone graft to address posterior glenoid bone loss in patients undergoing anatomical total shoulder arthroplasty. Methods: A systematic review of posterior glenoid bone-grafting in patients undergoing anatomical total shoulder arthroplasty was performed. Studies evaluating patient-reported outcomes, complications, and imaging assessments of the glenoid component as well as of bone graft structural healing and integrity following posterior glenoid bone-grafting were included. Data extracted included demographic characteristics, Walch classification, bone-grafting method, clinical outcomes measures, complications, radiolucency around the glenoid component, graft failure, posterior humeral head subluxation, and time of the latest follow-up. Results: Six studies met the inclusion and exclusion criteria. Ninety-four patients from these 6 studies underwent posterior glenoid bone-grafting with anatomical total shoulder arthroplasty. The mean age was 59.7 years, and the mean duration of follow-up was 5.7 years. Overall, 57% of the patients had an excellent postoperative Neer score. At the time of the latest follow-up, 28.7% had evidence of radiolucency and 35% had humeral head subluxation or instability. Thirteen patients (14%) underwent revision of the glenoid component by the time of the latest follow-up. Conclusions: The present study demonstrated a 28.7% complication rate, a 14% revision rate, a 17% graft failure rate, and a 35% rate of recurrence of posterior humeral head subluxation. Posterior glenoid bone-grafting to correct bone loss is associated with a substantial risk of postoperative complications. The treatment of posterior glenoid bone loss remains a challenge in patients undergoing anatomical total shoulder arthroplasty. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.